Automating the process of professional selection of pilots Civil Aviation - Харченко, В.П.; Чинченко, Ю.В. (Proceedings of National Aviation University (archive), 2006)
The principles of composition of target model of air traffic controller and supervisor are proposed. The features of professional activities of supervisor at air traffic units of Ukraine are considered.